2013
DOI: 10.1160/th13-02-0121
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerable coronary plaque: update on imaging technologies

Abstract: Several studies have been carried out on vulnerable plaque as the main culprit for ischaemic cardiac events. Historically, the most important diagnostic technique for studying coronary atherosclerotic disease was to determine the residual luminal diameter by angiographic measurement of the stenosis. However, it has become clear that vulnerable plaque rupture as well as thrombosis, rather than stenosis, triggers most acute ischaemic events and that the quantification of risk based merely on severity of the arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 211 publications
(214 reference statements)
1
26
0
1
Order By: Relevance
“…Modern histopathologic research has confirmed this hypothesis, demonstrating the presence of cells deriving from osteoblastic and osteoclastic lineage in areas of vascular calcification (2,3). These characteristics allow for the use of CT to assess calcification and generate a clinical calcification score, which is widely regarded as a sound index of the burden and extent of atherosclerotic plaque (4,5). However, a calcification score represents only a static picture, not the pathophysiologic behavior of plaque, and may not fully correlate with a patient's clinical status and cardiovascular risk (6)(7)(8).…”
mentioning
confidence: 95%
“…Modern histopathologic research has confirmed this hypothesis, demonstrating the presence of cells deriving from osteoblastic and osteoclastic lineage in areas of vascular calcification (2,3). These characteristics allow for the use of CT to assess calcification and generate a clinical calcification score, which is widely regarded as a sound index of the burden and extent of atherosclerotic plaque (4,5). However, a calcification score represents only a static picture, not the pathophysiologic behavior of plaque, and may not fully correlate with a patient's clinical status and cardiovascular risk (6)(7)(8).…”
mentioning
confidence: 95%
“…This factor makes it potentially useful for the identification of vulnerable plaque115 and individuals with high CVD risk 22, 64, 116…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…The pathological structure of atherosclerotic coronary arteries can be assessed by different imaging technologies [46]. Although PCI per se is not an imaging technology, this procedure is still the most commonly used in clinical practice (also because it allows a therapeutic approach) to investigate stenosis within coronaries.…”
Section: Statin-associated Benefits In Patients Admitted For Acs Undementioning
confidence: 99%